Kepemimpinan Strategis Dan Perubahan Pada Perguruan Tinggi - Elly Noer (EKONOMI & SOSIAL, 2019)
The world recently changed rapidly in all fields. Higher education is one of the sectors that cannot avoid these changing. An existed Higher education is able to survive at this time is a university that is always willing to make the strategy changing and culture of the organization. And it is also supported by the existence of a strategic leader in the organization. This study aims to know the impact of strategic leadership and organizational culture on changes in the organization of higher education in Surabaya, East Java. The research method used in this research is quantitative. This research population was 231 study programs with minimum accredited criteria B. The sampling technique used was purposive sampling, so the sample of this research was 72 study programs. Data analysis method used is Partial Least Square. The results showed that the strategic leadership and organizational culture each had a positive and significant influence on the changing in the organization of higher education in Surabaya, East Java.